Uncovering the Linkages Between Branding Strategy and Rural Tourism: A Systematic Literature Review - Yuliana Rakhmawati; Farida Nurul Rahmawati; Nikmah Suryandari; Netty Dyah Kurniasari (UPT Publikasi Ilmiah UNISBA, 2025)
Brand development in rural destinations has become increasingly vital in the tourism industry, as diverse attractions intensify competition for brand image. Previous research highlights the role of branding strategies in shaping these destination’s images. Therefore, this study aims to overview the branding strategies used in rural tourism development. This study employed a systematic literature review method to identify, evaluate, and interpret relevant research findings. Data were collected using Publish or Perish. Reduction was conducted through an inclusion-exclusion protocol. Using the Google Scholar and Scopus databases, 159 articles were collected, representing key themes and keywords for analysis. The PRISMA scheme mapped the literature, which was processed through descriptive and thematic analysis, resulting in 23 articles selected for analysis. Thematic analysis reveals three central clusters: destination branding which emphasize authenticity, cultural identity, and community participation; brand positioning which focus on competitive differentiation and tourist experience; and brand elements which highlight storytelling, visual identity, and culinary heritage.These findings suggest that rural branding strategies go beyond mere image creation by positioning local culture and heritage as integral components of sustainable tourism communication. The review contributes an integrated mapping of branding strategies in rural contexts and offers practical implications for policymakers and tourism stakeholders. Specifically, the study highlights the importance of identity-based branding strategies that strengthen competitiveness, foster community engagement, and support long-term rural development.